1980
DOI: 10.1115/1.3251540
|View full text |Cite
|
Sign up to set email alerts
|

Phase Change in Liquid Face Seals II—Isothermal and Adiabatic Bounds With Real Fluids

Abstract: Phase change effects in parallel and tapered liquid face seals are studied analytically. Both an isothermal and adiabatic model of low Reynolds number flow are considered by numerical integration of the descriptive equations for a real fluid. Real fluid thermodynamic properties are calculated for each step, using a computer program for the steam tables or thermodynamic properties of the fluid considered. Examples are presented for water. The general conclusions are: 1. For low leakage rate the isothermal model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Boiling can occur in such zones where liquid is saturated (Hughes et al, 1978;Hugues and Chao, 1980). The complex coupling of thermal distortions of the faces, heat dissipation in the film and phase change affect greatly the load capacity and the leakage rate of mechanical seals.…”
Section: Introductionmentioning
confidence: 98%
“…Boiling can occur in such zones where liquid is saturated (Hughes et al, 1978;Hugues and Chao, 1980). The complex coupling of thermal distortions of the faces, heat dissipation in the film and phase change affect greatly the load capacity and the leakage rate of mechanical seals.…”
Section: Introductionmentioning
confidence: 98%
“…Thus a given film thickness can be reached for two different load values (or balance ratio). However, this situation does not necessarily correspond to an unstable situation, as discussed in previous papers [5][6][7][8] where only steady-state simulations were performed. Brunetière and Apostolescu [30] showed that the dimensionless temperature rise in a liquid lubricated mechanical seal is a function of a dimensionless thermal loading parameter, the sealing number Se:…”
Section: Parametric Studymentioning
confidence: 88%
“…Several authors [5][6][7][8] studied phase change in steady state and demonstrated that the opening force due to the fluid pressure in the interface, when plotted versus the film thickness, can exhibit an unstable zone. This means that this force can increase with the film thickness, leading to an opening of the seal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li investigated the temperature field of the fluid film by means of FEM on the assumption that the properties of the fluid film were constant along the sealing dam [1] . Hughes and Chao analyzed the phase change of the fluid film in the liquid face seals and neglected the heat transfer from the outer surfaces of sealing rings into their surrounding sealed liquid [2] . Lebeck regarded the heat convection coefficient from the surfaces of the seal rings to the high pressure sealed liquid as a constant and built an actual seal model [3] .…”
Section: Introductionmentioning
confidence: 99%